A procedural approach based on cellular automata for the generation of spatial layout designs - Ng, Chelsea Shan Xian (2025)
Spatial layout planning is a complex architectural problem involving numerous constraints and potential solutions. Conventional methods can be tedious and time-consuming, prompting recent research toward automated layout generation to create more design alternatives and ease the process. Presented here is a procedural model for spatial layout design, inspired by methods in game design and based on cellular automata. The model considers user inputs such as geometry, topology (direct and indirect adjacencies), and privacy requirements to automatically generate design options. The generated layouts satisfy input requirements and are generated deterministically through specification of seeds that have virtually no upper limit. The proposed method aims to support architects and designers in the layout planning process by combining algorithmic efficiency of cellular automata with a top-down approach to adhere to user-defined constraints. This method also has potential for integrating additional design objectives and user interaction in future developments.